Technical efficiency of domestic commercial banks in Malaysia / Nurhazani Muhamad Ayub - Muhamad Ayub, Nurhazani
This study focuses on the technical efficiency of domestic commercial banks in Malaysia. The objective or the purpose of this study is to determine whether the banks are efficient inefficient in combining their input and output. In this study, the bank inputs acts as independent variables; net fixed assets and operating expenses. The dependent variables for this study are loans and advances, deposits, and investment securities. In order to make this study clearly defined, there are two models were created. To analyze the technical efficiency of domestic commercial banks in Malaysia, this study using ten domestic commercial banks in Malaysia. The time horizon ; during 1996 to 2005 which covers ten years. Technical efficiency is estimated by using intermediation approach to define bank input and output. This study assumed that banks transform net fixed assets and operating expense to produce loans and advances, deposits and investment securities. This study was using non-parametric approach, which is known as Data Envelopment Analysis (DEA), developed by Charnes, Cooper and Hodes (1978). DEA provides the mathematical formula in measuring technical efficiency scores. There are some previous researches have concluded that most of the inks are inefficient in combining their input and output in achieving the banks goals. his study can be used by the domestic commercial banks as their guideline to know their technical efficiency.